OPTIMIZATION OF COMPOSITION, STRUCTURE, PROPERTIES OF CONCRETE MIXTURE AND CONSTRUCTIONAL CLAYDITE-CONCRETE - Nikiforova, N. A.; Maslyaev, A. F. (Science and Transport Progress, 2010)
In the article the aspects of mutual influence of the resilience and cohesion characteristics of the concrete mortar ingredients on its physical and mechanical properties are considered.